Mental Health Providers' Assessment of Parents' Reactions to their Children's Elevated Depressive Symptoms. Issue 2 (4th November 2020) - Shapira, Amit; Volkening, Lisa K.; Markowitz, Jessica T.; Butler, Deborah A.; Laffel, Lori M.
Abstract: This study assessed parental reactions to the report of elevated depressive symptoms in a sample of 29 youth with type 1 diabetes (ages 8‐17 years; 48% female) who scored ≥15 on the Center for Epidemiologic Studies Depression Scale for Children (CES‐DC). We also assessed parental depressive symptoms and how the presence of such symptoms was linked to parental reactions to the report of a positive screening score in their children and subsequent acceptance of a mental health referral. Mental health professionals contacted parents to discuss elevated scores and offer a mental health referral. Two coders reviewed the documentation of phone contacts made by mental health professionals and categorized parental responses to their child's elevated CES‐DC score and the disposition plan. Youth and parent depressive symptoms were modestly correlated ( r = 0.21, P = .01). About half (55%, 16/29) of parents were unaware of their child's depressive symptoms. Only 14% (4/29) of youth were already receiving mental health care while 28% (8/29) of parents accepted a referral. Parents with depressive symptoms were frequently unaware of their child's symptoms. Findings provide insight into parental reactions to learning of their child's depressive symptoms and highlight the need for more research on parental mood and reactions to their child's positive screen for depressive symptoms, as a potential barrier to mental health referral acceptance.